Early Modern Women in Conversation - Larson, K. author. aut Link
XII, 218 p.
Keywords: In 16th and 17th century England conversation was an embodied act that held the capacity to negotiate, manipulate and transform social relationships. Early Modern Women in Conversation illuminates the extent to which gender shaped conversational interaction and demonstrates the significance of conversation as a rhetorical practice for women.